PENERAPAN SISTEM AKUNTANSI DALAM PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN STANDAR AKUNTANSI KEUANGAN (SAK) PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) (Studi Kasus pada Warung Susu Shi-Jack di Surakarta) - Sari, Intan Prastika; Harimurti, Fadjar; Saptantinah, Dewi (Universitas Slamet Riyadi, 2020)
The purpose of this research is to implement an accounting system in the preparation of financial statements at the Shi Jack Milk Shop Jl. Captain Mulyadi, Surakarta based on Financial Accounting Standards (SAK). The results showed that the preparation of an accounting system based on Indonesian GAAP was carried out by compiling financial statements which include income statements and statements of financial position. The income statement is prepared in accordance with SAK EMKM as a reference used to prepare financial statements for small and medium businesses, so they can find out the amount of net income. The report on the financial position of the researcher compiled for Warung Shi Shi Jack contains information about assets and liabilities, so that it can be easier to prepare financial reports and see estimates that occur in daily company activities, so that management can control any company expenses to support its operations or operations.